Healthcare system development in the Middle East and North Africa region: Challenges, endeavors and prospective opportunities - Katoue, Maram Gamal; Cerda, Arcadio A.; García, Leidy Y.; Jakovljevic, Mihajlo (Frontiers in Public Health, 2022)
Background: Countries in the Middle East and North Africa (MENA) region have been investing in development of their health systems through implementing reforms to improve health care delivery for their nations. However, these countries are still facing challenges in providing equitable, high quality health care services. There is limited published literature supporting the previous and ongoing attempts that have been made to improve health system performance in MENA countries. Aims: This review aims to describe experiences of health system development efforts in the MENA region, highlight progress, identify challenges that need be addressed and future opportunities to achieve responsive and efficient health systems. It also aimed to provide recommendations to further support these health systems toward evolution and performance improvement. Methods: A literature review was conducted by searching different databases including PubMed, Scopus, Google Scholar and other electronic resources to identify articles and publications describing health systems development in the MENA region from 1975 to 2022. It also included grey literature, reports and policy and planning documents by international organizations. The identified references were reviewed to extract, analyze, organize and report the findings. Results: The review revealed emerging evidence describing governmental initiatives to introduce health reforms at different levels in the MENA countries. These include initiatives targeting the various elements controlling health system reform: financing, payment, organization, regulation and behavior of providers and consumers. There are several challenges facing the health systems of MENA countries including the rising burden of chronic dis¬eases, inequitable access to health services, deficiency in health workforce, shortage in the use of effective health information systems and leadership challenges. The review identified several key areas that can benefit from further improvement to support health system reforms. These include improving the structure, organization, financing of health systems, healthcare workforce development, effective data management and engagement of key stakeholders to achieve adequate health reforms. Conclusion: The MENA countries have made significant steps to improve the performance of their health systems; yet achieving a comprehensive health reform will require collaboration of various stakeholders including health policy makers, healthcare professionals, and central to the success of the reform, the patients.